Caracterização microestrutural do aço SAE 1080 após diferentes tratamentos térmicos - Ribeiro, Joshua Alyson Freitas (2017)
Thermally treated steels with eutectoid composition are normally used in subway tracks. To obtain the desired mechanical properties for the especific aplications, the material may be submitted to some heat treatments, such as, Plane Annealing, Normalization and Quench. The Heat Treatments are extremally importante, because it is a method to improve the mechanical properties without changing the chemical composition.In this study, the microstructural caracterization was evaluated onsubway track samples that were provided by Laboratory of Research and Tecnollogy in Welding. Metalographic analyses were done after different heat treatments in SAE 1080 Fe-C steel samples with the aim of verifying the influence in the microstructural and mechanical aspects of the samples. The material as recieved presented a matrix with, aproximally, 100% perlithic composition and due to the heat treatments, the material went through phase transformations, thus altering the interlamellar spacing and by consequence its hardness.